The history of architecture and art and how it is seen by tourists - Kaczmarek, Sylwia (Turyzm/Tourism, 2013)
The article presents the relation between the presence of works of art (buildings, sculptures, paintings) at different locations in the world, and tourism. The main theoretical and practical questions include the following: How important is knowledge of the history of art for seeing works of art? What other factors make modern travellers visit places where they can find these works of art?